Motives for Texting During Early Adolescence - Yau, Joanna C.; McPartlan, Peter; Reich, Stephanie M. (Frontiers in Human Dynamics, 2021)
Research on teen texting typically focuses on the frequency of texting, but not the motives behind it. We surveyed 130 young adolescents (M = 12.41 years) and identified user-profiles based on their motives for texting. We examined whether the profiles were related to phone habits that may affect health and learning (e.g., phone placement when sleeping). Participants were asked how often they texted someone when they were excited, proud, frustrated, angry, anxious, sad, needed help with homework, wanted to make plans, and needed advice (0 (never) to 4 (always)). Using k-means clustering, we identified six profiles. Frequent-Texters texted frequently for all purposes while Selective-Texters rarely texted for any reason. A different group of high frequency texters: Positive-Frequent-Texters frequently texted to express positive emotions, ask for advice, and for practical reasons, but rarely to express negative emotions. Similarly, there was another group of low frequency texters: Positive-Selective-Texters rarely texted except to express positive emotions. Moderate-Texters texted less frequently than Frequent-Texters and more frequently than Selective-Texters for all purposes. Positive-Practical-Moderate-Texters texted more frequently to share positive emotions and for practical reasons than Moderate-Texters, but texted less frequently than Frequent-Texters. We found that profiles were a function of gender, texting experience, and Fear of Missing Out (FOMO). Frequent-Texters were girls that started texting at a marginally younger age than Selective-Texters and had high FOMO scores. Profile membership was related to phone habits. For instance, when sleeping, Frequent-Texters were more likely than other groups to have their phones on or next to the bed. When doing homework, Selective-Texters were less likely to keep their phones on or near them. Interestingly, Positive-Frequent-Texters were more likely to have the ringer on or to have their phone on vibrate while doing homework, but not more likely to keep their phones nearby. Suggesting a preference for awareness of notifications but possible self-regulation effort to keep their phones at a distance. Given that texting is a common communication method, it is important to understand why youth text and how those reasons relate to healthful and risky phone habits.